ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN PADA PT. HATTEN BALI DI KOTA DENPASAR - Puspita Sari, Kadek Martika; Kusumadewi, Ni Md. Wulandari (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of marketing mix variables simultaneously and Parsian on sales volume in PT. Hatten Bali. The research object is the marketing mix and volume of sales at PT. Hatten Bali. In this study, the population was around the end consumers (buyers) PT. Hatten Bali. Sampling technique used was random sampling with a sample size of 95 people. Collecting data using a Likert scale questionnaire. Data analysis techniques using multiple linear regression. The results showed the product, price, distribution and promotion channels simultaneously significant effect on the volume of sales at PT. Hatten Bali with F count = 1586.96 sig = 0.00. Product, price, distribution channels and promotions partially significant effect on the volume of sales at PT. Hatten Bali. Distribution channels are independent variables were the dominant influence on the sales volume.
Keywords: Product, Pricing, Distribution Channel, Promotion, Sales Volume